TINDAK TUTUR EKSPRESIF DALAM KOLOM KOMENTAR INSTAGRAM @PKUCITY TERKAIT KASUS ABDUL WAHID 2025/2026 - Dian Nurul Fitra; Rika Ningsih (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study examines expressive speech acts used by netizens in the Instagram comment section of @pkucity regarding the Abdul Wahid case. The research was motivated by the increasing use of social media as a platform for expressing opinions, emotions, and responses to social issues. The objective of this study was to identify and describe the forms of expressive speech acts found in netizens’ comments. This research employed a qualitative approach using content analysis. The data consisted of written comments collected from Instagram posts related to the Abdul Wahid case that generated significant public interaction. Data were gathered through documentation, reading, and note-taking techniques and analyzed through coding, classification, interpretation, and reporting. Data validity was ensured through credibility, transferability, dependability, and confirmability. The findings revealed that condemnation was the most dominant expressive speech act (56 data), followed by criticism (40 data), complaints (20 data), expressions of sadness (17 data), and blaming (10 data). Expressions of praise and congratulations were found in two instances each, while gratitude, forgiveness, and condolences were not identified. The results indicate that social media communication is largely dominated by negative expressions reflecting public disappointment, criticism, and emotional responses to social issues. These findings demonstrate that the meaning of speech on social media is strongly influenced by the context and communicative intentions of the speakers.